2009
DOI: 10.1242/jcs.052233
|View full text |Cite
|
Sign up to set email alerts
|

A role for the DNA-damage checkpoint kinase Chk1 in the virulence program of the fungusUstilago maydis

Abstract: During induction of the virulence program in the phytopathogenic fungus Ustilago maydis, the cell cycle is arrested on the plant surface and it is not resumed until the fungus enters the plant. The mechanism of this cell cycle arrest is unknown, but it is thought that it is necessary for the correct implementation of the virulence program. Here, we show that this arrest takes place in the G2 phase, as a result of an increase in the inhibitory phosphorylation of the catalytic subunit of the mitotic cyclin-depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
61
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(72 citation statements)
references
References 40 publications
6
61
1
3
Order By: Relevance
“…Any condition resulting in inhibition of Cdk1-Clb2 complex produces both a G2 delay/arrest as well as the induction of strong polar growth. These conditions include mutations affecting either the Cdk1-Clb2 complex directly (García-Muse et al., 2004); the balance of inhibitory phosphorylation via Wee1 or Cdc25 activities (Sgarlata and Pérez-Martín, 2005a;Sgarlata and Pérez-Martín, 2005b); the response to checkpoint activation such as the DNA damage response (Pérez-Martín, 2009); or the response to developmental cues, such as the virulence program (Mielnichuk et al, 2009). We observed that conditional removal of wee1 or expression of a cdk1 allele refractory to inhibitory phosphorylation prevented the hyperpolar growth observed in ukc1 mutants.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Any condition resulting in inhibition of Cdk1-Clb2 complex produces both a G2 delay/arrest as well as the induction of strong polar growth. These conditions include mutations affecting either the Cdk1-Clb2 complex directly (García-Muse et al., 2004); the balance of inhibitory phosphorylation via Wee1 or Cdc25 activities (Sgarlata and Pérez-Martín, 2005a;Sgarlata and Pérez-Martín, 2005b); the response to checkpoint activation such as the DNA damage response (Pérez-Martín, 2009); or the response to developmental cues, such as the virulence program (Mielnichuk et al, 2009). We observed that conditional removal of wee1 or expression of a cdk1 allele refractory to inhibitory phosphorylation prevented the hyperpolar growth observed in ukc1 mutants.…”
Section: Discussionmentioning
confidence: 63%
“…Different signaling cascades seem to converge on the regulation of Cdk1 inhibitory phosphorylation in U. maydis. These cascades include the b-dependent pathogenic program (de Sena-Tomás et al, 2011;Mielnichuk et al, 2009), DNA damage response (Mielnichuk and Pérez-Martín, 2008;Pérez-Martín, 2009), the Cell Wall Integrity pathway (Carbo and Pérez-Martín, 2010) and the pheromone response pathway (S. Castanheira and J.P.-M., unpublished data). In general cell cycle has been considered as a final effector, which is accordingly modified upon previous integration of the various signaling cascades in the cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research from our group has shown that efficient cell cycle arrest during the infective filament formation requires the cooperation of elements from the DNA damage response (DDR) cascade, such as the kinase Chk1 and its upstream activating kinase Atr1 (de Sena-Tomas et al, 2011;Mielnichuk et al, 2009;PerezMartin, 2009). During the early stages of formation of the infective hypha, the Chk1 kinase is activated for a short period of time, resulting in a transient G2 cell cycle arrest (Mielnichuk et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…These kinases are broadly conserved regulators (Abraham 2001;Bartek and Lukas 2003). Recent work performed in the phytopathogenic basidiomycete Ustilago maydis (Mielnichuk et al 2009;de Sena-Tomas et al 2011;Perez-Martin and de Sena-Tomas 2011) suggested a role for the kinases Atr1 and Chk1 in the regulation of the dikaryotic cell cycle. U. maydis cells defective in these kinases showed impaired dikaryon proliferation.…”
mentioning
confidence: 99%